Potential and genetic divergence in advanced common bean populations (Revista de Ciências Agroveterinárias, 2008)
The selection success in a breeding program depends on the existence of genetic variability. The objective of this work was to evaluate the level of genetic divergence among 24 common bean genotypes, being 22 F5 populations of the Common Beans Genetic Breeding Program of Epagri/Cepaf. Treatments were arranged in complete randomized blocks with four replications. The genetic divergence of eight agronomical important traits was estimated by the generalized distance of Mahalanobis. The genotypes were grouped by the method of Tocher and next neighbor. Populations CHP 97-05 and CHP 97-08- 21 were identified as the most promising. They will be further evaluated to obtain new lines. These two populations can also be crossed with populations identified as divergent and complementary in agronomic traits.
Keywords: Phaseolus vulgaris; variability; genetic dissimilarity.